Validation of a new immunofluorescence antibody test for the detection of Leishmania infantum infection in cats - Iatta, Roberta; Trerotoli, Paolo; Lucchese, Laura; Natale, Alda; Buonavoglia, Canio; Nachum-Biala, Yaarit; Baneth, Gad; Otranto, Domenico (Parasitology research (1987), 2020)
The prevalence data of Leishmania infantum infection in cats are characterized by a large variability mainly attributed to the differences in diagnostic techniques. In the absence of consensus about the method of choice for diagnosing feline leishmaniosis, the performance of a new immunofluorescence antibody test (IFAT) was herein analytically described by the comparison with IFAT commonly used for the diagnosis of canine leishmaniosis (i.e., IFAT-OIE) and a laboratory enzyme-linked immunosorbent assay (ELISA). Sera of cats living in visceral leishmaniosis–endemic ( n = 105) and visceral leishmaniosis–non-endemic ( n = 50) areas were tested by the above methodologies and real-time PCR (qPCR). The most frequent result was represented by triple negativity to the three tests (IFAT-OIE, ELISA, and qPCR) in 42.9% and 80% cats from endemic and non-endemic areas, respectively. Bayes latent class analysis gave an output probability of 34.1% (posterior standard deviation, psd = 5.4%) of true L . infantum cases (TCL) which represent the true estimated prevalence of infection. The sensitivity of each variable contributing to define the TCL was 24% (psd = 6.3%) for qPCR, 78.8% (psd = 8.7%) for ELISA and 91.8% (psd = 5.2%) for IFAT-OIE. The probability to be a TCL was 94.5% for the sample from an endemic area. The cross-validation of the new IFAT by a logistic model correctly identified as positive 80.7% of subjects defined as TCL and negative 89.9% as not TCL, respectively, by the Bayesian model. The study results estimate a good accuracy of the IFAT in predicting cats exposed to L . infantum . Therefore, this procedure may be beneficial for screening cat populations for a better understanding of the epidemiology of feline leishmaniosis.